Analysis of the work of Theodore Draiser and the novel “American tragedy” on the traditions of critical realism - Salimova , Hulkar (The Lingua Spectrum, 2025)
This article examines the literary works of Theodore Dreiser and his contribution to the development of critical realism. Special attention is given to his novel “An American Tragedy,” which highlights social inequality, the gap between wealth and poverty, and the erosion of human values. The influence of Dreiser’s works on Uzbek literature is also analyzed, particularly in relation to Abdulla Qodiriy’s works, exploring the realism elements shared between them.